Seperangkat Alat Shalat Sebagai Mahar Pernikahan Perspektif Hadis - Karomah, Hikmatul (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2023)
Mahar is a form of Islamic concern for a woman, so as a form of respecting her position, she is given the right to receive a dowry (dowry) when she wants to marry. Mahar is closely related to marriage. Even though it is not included in the pillars of marriage, the dowry remains the wife's right that must be fulfilled by the husband. It is common in society, especially in rural areas, to make a set of prayer tools as a wedding dowry, even though there are actually various types of dowry that can be submitted, such as a sum of money and jewelry. The purpose of this study is to describe the eligibility status of a set of prayer tools used as a wedding dowry today in a hadith review and differences of opinion regarding the criteria for dowry in marriage. Data collection in this study used a qualitative approach which included observations, interviews, and literature review which were then presented in the form of descriptive narratives based on hadiths and the opinions of several Imams of Madzhab. This research resulted in several reasons for determining the dowry for marriage, especially in rural areas, namely: 1) Adhering to the Al-Quran and Hadith, 2) Understanding that Islam does not determine the minimum amount of dowry that must be given, because the abilities and abilities of people are different although the dowry (dowry) must meet the criteria in Islam. 3) Have high sympathy and empathy between people so there is no ego to burden and bring each other down.